Les sites de l'eglise Sainte Cecile et de l'ancienne agglomeration de Guran en Istrie (Croatie): dixieme campagne de fouilles archeologiques - Terrier, Jean; Marić, Iva; Jurković, Miljenko (2012)
The main results of the 2011 excavations campaign on the site of Guran in south Istria concern the fortified early medieval settlement the origin of which is dated to the Carolingian perion and is abandoned in the late Middle ages, and the church of St Cecilia situated some few hundred meters to the north of the settlement.The results of the excavations of St Cecilia were particularly rich, revealing at least six phases prior to the existing church.
Projekt MZOS
FRA